(untitled) (Bangladesh Heart Journal, 2020)
Background: Acute Myocardial Infarction is the leading cause of morbidity and mortality throughout the world. Its prevalence among developing countries has increased significantly over the past two decades. Acute myocardial infarction is associated with electrolyte imbalance most commonly hypomagnesemia and hypokalaemia. Both are associated with ventricular arrhythmia which can lead to increase hospital mortality and morbidity. Objectives: To find out association of hypomagnesemia with ventricular arrhythmia in patients with acute myocardial infarction. Methods: Patients with acute myocardial infarction admitted in the department of Cardiology, DMCH, within the study period and who fulfilled the inclusion and exclusion criteria were taken as study sample. Informed consent was taken from all patients and then the patients were evaluated by detailed history, clinical examination and relevant investigations. Serum magnesium level was measured after admission. The sample population was Grouped into Group A(Acute myocardial infarction with normal serum magnesium) and Group B(Acute myocardial infarction with hypomagnesemia). Patients were followed up regularly till discharge or death for evidence of ventricular arrhythmia. Then the obtained data was analysed with SPSS 22.0. Results: Among 110 patients of Acute MI, 44 patients were in Group A who had plasma magnesium level e”0.7 mmol/ l and 66 patients were in Group B who had plasma magnesium level <0.7 mmol/l. Incidence of hypoagnesemia was 60% and more common in male. Male vs female percentage of hypomagnesemia were 61% vs 39%. Mean age was 54.16±11.72 yrs vs 57.52±10.59 yrs in group A vs group B. On admission serum magnesium level was 0.9218 vs 0.523 mmol/L( group A vs group B). The study showed that group B patients were more haemodynamically unstable and mean SBP and DBP were found 89.39±19.93 and 60.67±11.56 mm-Hg respectively. Troponin I was markedly increased in group B than A (i.e 4.7±1.79 vs 14.6±4.3 vs ng/ml). Adverse cardiac events such as cardiogenic shock (group A vs group B = 11.36% vs 28.27%) and ventricular arrhythmias(group A vs group B = 34% vs 72.73%) were also higher in group B than group A. Mean hospital stay for group B patient was higher than group A(6.78±0.85 vs 5.31±0.35 days). The study result showed that ventricular arrhythmia is negatively correlated with serum magnesium and the correlation coefficient was - 0.541. It also showed that serum Magnesium is positively correlated with Potassium(r= 0.831, p<0.01) and Calcium(r= 0.902, p<0.001). Multiple logistic regression analysis showed that hypomagnesemia is an independent risk factor for ventricular arrhythmia. Conclusions: This study showed that in patients with acute myocardial infarction, hypomagnesemia is common and it is significantly associated with ventricular arrhythmia. So the presence of hypomagnesemia should alert the physicians to adopt corrective measures as it increases both mortality and morbidity. Bangladesh Heart Journal 2020; 35(1) : 39-46